EVALUATION OF ELECTRICAL RESISTANCE SENSORS AND TENSIOMETERS EQUIPPED WITH TENSION TRANSDUCERS FOR SOIL WATER POTENTIAL DETERMINATION (Revista de Ciências Agroveterinárias, 2004)
Electronic sensors have been increasingly used for soil water measurement, which is important for plant growth and for rational water use. The aim of the present study was to assess the performance of electrical resistance sensors (SRE) comparatively to tensiometers equipped with tension transducers (TT). TT’s coupled to 0.3-meter-long tensiometers were assembled on porous plates and submitted to increasing tensions ranging from 1 to 14,5 kPa. Both TT’s and SRE were installed in a box containing an air-dried fine earth sample of a red latosol, which was saturated with water and air-dried. The soil was then saturated with a potassium chloride solution. Finally, sensors were installed in the field for a fourmonth period. The results revealed the values showed a difference of 3 kPa and that salinity did not affect significantly the correlation between the data obtained from both sensors. Both SRE and TT’s showed similar performance in the wet range where the experiment was carried out and in the field, being quite useful to monitor soil water content.
Keywords: soil water; matric potential; salinity.